Republic of Moldova : Staff Report for the 2002 Article IV Consultation, First Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility and Request for Waiver of Performance Criteria. (IMF Staff Country Reports; Country Report, 2002)
This paper examines the Republic of Moldova's 2002 Article IV Consultation, First Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility, and a Request for Waiver of Performance Criteria. Moldova has followed sound macroeconomic policies, and most financial targets under the 2001 program were met. Structural reforms slowed in 2001, but gained momentum in 2002. Implementation of most program benchmarks was delayed because of a change in government. The focus now is on fiscal reforms and on improvements in the legal framework.